2015
DOI: 10.1186/s12909-015-0457-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimum number of procedures required to achieve procedural skills competency in internal medicine residents

Abstract: BackgroundProcedural skills training forms an essential, yet difficult to assess, component of an Internal Medicine Residency Program. We report the development of process of documentation and assessment of procedural skills training.MethodAn explanatory sequential mixed methods design was adopted where both quantitative and qualitative information was collected sequentially. A survey was conducted within the Department of Internal Medicine at The Aga Khan University Hospital, Karachi, Pakistan to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The required minimal thresholds were extrapolated from the available literature on procedural competency training. [13,14] Fulfilling all these criteria should render the diagnostic radiology resident competent to perform these procedures under indirect supervision. Otherwise, the resident will continue to require direct procedural supervision [ Figure 2].…”
Section: Resultsmentioning
confidence: 99%
“…The required minimal thresholds were extrapolated from the available literature on procedural competency training. [13,14] Fulfilling all these criteria should render the diagnostic radiology resident competent to perform these procedures under indirect supervision. Otherwise, the resident will continue to require direct procedural supervision [ Figure 2].…”
Section: Resultsmentioning
confidence: 99%
“…Work hours, similarly, are known to vary significantly between interventional and non-interventional specialties: while the former are not limited to the field of Surgery, Surgery as a field is by definition interventional [ 14 ]. This dichotomy is particularly severe during residency, where procedural exposure in medical training is often limited to those pursuing fellowship training [ [15] , [16] , [17] ]. A systematic review by Peel et al identified three key factors in medical graduates’ decisions to pursue a career in a surgical discipline, rather than a non-surgical one, supporting the claim that the streams are in some way unique: gender (an umbrella term including gender discrimination, a perceived deterrence to a career in surgery for women, gender bias in career advancement, lack of female role models, and the impact of parenting and lifestyle considerations), the availability of surgical exposure and training in medical education, and—most heavily studied—the lifestyle and perception of “work-life balance” of a career in surgery [ 18 ].…”
Section: Divides Between Medicine and Surgerymentioning
confidence: 99%
“…This model of developing training programs is particularly useful if the focus of the program is targeted toward changing participant behavior and improving performance. ADDIE is increasingly being adopted in industries such as health care ( 13 ). Recent studies have successfully adopted the ADDIE model to improve patient safety, procedural competency, and disaster simulation ( 14 , 15 ).…”
Section: Background and Rationale For Educational Activitymentioning
confidence: 99%